MANDAT ILAHI DALAM PERAN SOSIAL BUDAYA BAGI PENGINJILAN DI THAILAND - Andreas Eko Nugroho; Jessica E. Chen (STT Bethel The Way, 2019)
The current phenomenon is that many of the missionaries in Thailand are evangelizing without special training on Thai socio-culture and lacking in Biblical content, so they engage in ineffective evangelism, meaning they do not set up a relevant evangelistic strategy to evangelize the Thai people. The Research conducted that Author doing for this thesis is qualitative and exegetical studies of the Biblical text, and also doing some interview with some people who has a competent in their side. The Author recommends that missionaries who wish to do an evangelistic ministry in Thailand attend an evangelistic training and study more about Thai social culture including Thai languages, as well as deeper study of the Bible concerning at least one year, so that the service is done more leverage